Analisa kekuatan mekanik pengaruh perendaman dan penekanan pada komposit berbahan serat mengkuang - Sutrisno Sutrisno; Azmal Azmal (Universitas Muhammadiyah Metro, 2020)
This study aims to determine the effect of mechanical properties, namely the tensile strength, bending and impact of the composite fiber mengkuang (pandanus artocarpus griff) without immersion and with immersion of 5% NaOH with an immersion time of 1 hour. Then the blending and casting process is carried out to form a composite material with 20% fiber and 80% resin binder with a catalyst content of 1% and pressurized with press variations of 5 kg, 10 kg, and 15 kg. The results of the blending and casting process are made according to the testing standard and then testing the mechanical properties. The results of tensile, bending and impact testing showed that for 1 hour immersion with a pressure of 15 kg the highest value was tensile strength of 13.75 N / mm2, bending strength of 33.61 N / mm2 and impact strength of 152.32 J / mm2. Whereas the form of the composite fiber of the decomposed fiber is the binder and the fiber breaks evenly at the same point and the fiber is not pulled from the metric.Keywords: composites, resins, mono fiber, mechanical properties